Charitable donations: Empirical evidence from Brunei - Lwin, Michael; Phau, Ian; Lim, Aaron (Emerald Group Publishing Limited, 2013)
Purpose – This paper aims to explore the demographic and psychographic characteristics of Bruneians in relation to charitable donation behaviour. Design/methodology/approach – Data were collected via an intercept approach at five major intersections of the central business district in the city of Brunei. Data were analysed using SPSS, with factor analysis being conducted before applying a series of t-tests and ANOVAs. Findings – Overall there is no relationship between age, income and gender, and donating behaviour. Results show that perceived generosity does not play an important role in Brunei compared to previous studies. The cause of this phenomenon could be due to the influence of the Bruneian culture. That is, the government takes a large responsibility for charitable events in Brunei and for this reason charitable donations from citizens are limited. Analysis also showed the importance of religion in predicting donation behaviour. Research limitations/implications – Further research in this paper should attempt to make more cross-cultural comparisons of donor characteristics. This would provide a more holistic perspective on donor behaviour and thus assist managerial decisions in the marketing of charities. The effects of religiosity on donation behaviour should be further analysed to ascertain the variances of donation behaviour across cultures with high dominance of religion.Originality/value – The principal contribution of this paper is that it provides insights into the nuances and characteristics of Bruneians in relation to attitudes and behaviour towards charitable donations.